COVID-19 infection and its deadly cytokine storm in a young obese adult. Issue 4 (3rd July 2020) - Abbas, Sundas; Ahmad, Ayaz; Lacasse, Alexandre
ABSTRACT: SARS-CoV-2 is a novel coronavirus that was initially described in Wuhan China in December 2019. In the USA (US), the person to be diagnosed with the novel Coronavirus infection (COVID) was on 19 January 2020. On 18 March 2020, a 31-year-old morbidly obese African American woman presented with severe dyspnea with associated hypoxemia, fever and bilateral interstitial pulmonary ground glass infiltrates consistent with viral pneumonitis. Nasopharyngeal PCR testing was positive for SARS-CoV-2. Despite initiation of hydroxychloroquine and azithromycin along with supplemental oxygen therapy, rapid disease progression consistent with cytokine release syndrome ensued, leading to initiation of mechanical ventilatory support. Anti-Interleukin (IL)-6 receptor monoclonal antibody (tocilizumab) was administered. Acute respiratory distress syndrome (ARDS) leads to refractory hypoxemia and demise. Severe morbid obesity as well as race may be unidentified risk factors for the development of severe Illness in patients with COVID-19.